2020
DOI: 10.1107/s2053229620006701
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the dissolution–recrystallization structural transformation (DRST) of copper(II) complexes: a combined crystallographic, mass spectrometric and DFT study

Abstract: Methanol- and temperature-induced dissolution–recrystallization structural transformation (DRST) was observed among two novel CuII complexes. This is first time that the combination of X-ray crystallography, mass spectrometry and density functional theory (DFT) theoretical calculations has been used to describe the fragmentation and recombination of a mononuclear CuII complex at 60 °C in methanol to obtain a binuclear copper(II) complex. Combining time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It seems that EtOH is not a good solvent for crystals of 3 and just some parts of crystals solved in it and recrystallized as compound 1 . This result showed that transformation from 3 to 1 is possible through the DRST process. ,, It should be noted that after 1 month a transformation (SC–SC or DRST) from 3 to 2 was not observed.…”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It seems that EtOH is not a good solvent for crystals of 3 and just some parts of crystals solved in it and recrystallized as compound 1 . This result showed that transformation from 3 to 1 is possible through the DRST process. ,, It should be noted that after 1 month a transformation (SC–SC or DRST) from 3 to 2 was not observed.…”
Section: Results and Discussionmentioning
confidence: 76%
“…Solid-state structural transformations of CPs have been attracting high attention recently. Also, there are a few reports on the structural transformation of solid samples of CPs and discrete complexes in solution through dissolution–recrystallization structural transformation (DRST). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Although this event is rather rare, there are some reports about it. In a few interesting cases, supramolecular isomers were formed in the reaction vessel concomitantly. Although structural transformation of CPs in the solid phase is highly regarded, there are few studies on the structural transformation in the liquid phase in CPs, especially through dissolution–recrystallization structural transformation (DRST). ,,, …”
Section: Introductionmentioning
confidence: 99%
“…The title compound contains a binuclear complex. As is shown in the Figure, [12,13]. In addition, the benzotriazole rings in adjacent molecules are parallel, with an average interplanar distance of 3.89 Å, thus π-π interaction cannot be ruled out.…”
Section: Commentmentioning
confidence: 99%